Urban transportation systems and governance in the Klang Valley, Malaysia - Raja Ariffin, Raja Noriza; Zahari, Rustam Khairi (2009)
This paper analyses the governance of urban transportation system in the Klang Valley, Malaysia, focusing on institutional issues. The Klang Valley was chosen as the study area due to its phenomenal growth in the last two decades that affected the administration of its urban transportation system. The lack of synergy in the administration of the system has resulted in an adverse impact on its efficiency. Interviews was utilised as the main research instrument. Through the examination of the practices, attitudes and beliefs of those working in the transport related field have shed some light on the relationship between agencies and the impact that these have upon transportation system in the Klang Valley. Other than interviews, these examinations involved investigating the history and current status of the policy development, implementation as well as administration, which were obtained through an examination of government documentation, archival records, and observation. The results indicate that there are four barriers that resulted in the inefficiency of the urban transport system in the Klang Valley, which are institutional issues, political issues, cultural and ideological issues, and finally, policy issues. However, as mentioned before, this paper will specifically focus on institutional issues as one of the main factors in urban transport governance in the Klang Valley, Malaysia.